Optical properties of polyimides films treated by nanosecond pulsed electrical discharges in water. (13th December 2017) - Sava, Ion; Kruth, Angela; Kolb, Juergen F.; Miron, Camelia
Abstract: Fluorinated polyimide films containing cobalt chloride based on hexafluoroisopropylidenediphthalic dianhydride and 4, 4′-diamino-3, 3′-dimethyl diphenylmethane were treated by nanosecond pulsed electrical discharges generated in distilled water. The polyimide films have been characterized by Fourier transform infrared (FTIR) spectra and contact angle measurements, optical transmission spectroscopy, and fluorescence spectroscopy. Significant changes in some intrinsic fluorescence features, such as the intensity and position of the emission peak, have been observed during exposure to water plasma. These effects have been considered to correlate with the development of specific chemical interactions between the liquid and the macromolecules, including the formation of hydrogen bridges. A slight increase in surface hydrophobicity was observed after plasma treatment. FTIR spectra showed a decrease in the intensity of the absorption band and an opening of the imide ring, depending on the treatment time.